2020
DOI: 10.1002/tafs.10205
|View full text |Cite
|
Sign up to set email alerts
|

A Complete Fisheries Inventory of the Chulitna River Basin, Lake Clark National Park and Preserve, Alaska: Example of a Minimally Disturbed Basin

Abstract: Because of mineral mining threats in the headwaters that drain into Lake Clark National Park, we implemented a baseline ecological survey of the Chulitna River basin through the use of a probability study design. A total of 49 wadeable stream and raftable river sites were sampled for fish assemblages, multiple physical habitat structure variables, and multimeter chemistry (dissolved oxygen, conductivity, pH, and water temperature) by the using standard methods that are employed in the United States Environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Ode et al (2011) found instream habitat cover, fine sediment and bed stability severely degraded in 20–40% of California stream length; riparian disturbances and riparian vegetation cover complexity, respectively, exceeded moderately degraded thresholds in 40% and 25% of the stream length. Hughes et al (2020) found no riparian human disturbance, 26–66% instream habitat cover, and 55–64% riparian woody vegetation cover in a probability survey of the stream and river length in 2 sub-basins of the roadless Chulitna River basin in Alaska. In the southeastern U.S., Jackson et al (2015) reported that conversion of riparian forest to grass resulted in reduction of instream habitat complexity (width variability, wood, coarse bed material), reduced riffle-pool structure, and increased streambed fine sediments.…”
Section: Discussionmentioning
confidence: 86%
“…Ode et al (2011) found instream habitat cover, fine sediment and bed stability severely degraded in 20–40% of California stream length; riparian disturbances and riparian vegetation cover complexity, respectively, exceeded moderately degraded thresholds in 40% and 25% of the stream length. Hughes et al (2020) found no riparian human disturbance, 26–66% instream habitat cover, and 55–64% riparian woody vegetation cover in a probability survey of the stream and river length in 2 sub-basins of the roadless Chulitna River basin in Alaska. In the southeastern U.S., Jackson et al (2015) reported that conversion of riparian forest to grass resulted in reduction of instream habitat complexity (width variability, wood, coarse bed material), reduced riffle-pool structure, and increased streambed fine sediments.…”
Section: Discussionmentioning
confidence: 86%
“…(2) They allow rigorous statistical estimation of the channel length of the entire river basin with known confidence limits (Herlihy, Larsen, Paulsen, Urquhart, & Rosenbaum, 2000). (3) Because they are random approaches, sites are not selected for convenience, thereby avoiding biased conclusions in ecological assessment studies, including in studies across difficult and unroaded subtropical and subarctic terrains (Hughes, Boxall, Herlihy, Adams, & Young, 2020;Jiménez-Valencia et al, 2014).…”
mentioning
confidence: 99%